Role of Business Intelligence Systems in Decision Making Support in an Enterprise : Review of BI Practical Application - Ziora, Leszek (Rola systemów business intelligence we wspomaganiu podejmowania decyzji w przedsiębiorstwie. Przegląd wybranych zastosowań praktycznych, 2009)
The most important role of Business Intelligence systems in an enterprise is the support of decisions at all levels of management what leads to the improvement of competitive advantage of a particular organization. BI environment becomes an integral part of the decision making process. The application of those systems in different areas of business activity for instance in controlling or telecommunication as it is presented has also an impact on the increase of work effectiveness. Data warehouses, OLAP, data mining and reporting help to improve the quality of decision making process and the efficacy of same decisions as well.A Business Intelligence system may also simplify access to business information through the use of information catalogue that documents decision support objects.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 55, s. 463-471
Keywords: Business Intelligence; decision support; data warehousing